Deep vein thrombosis and venous thromboembolism in trauma. Issue 2 (April 2018) - Ruskin, Keith J.
Abstract : Purpose of review: Deep vein thrombosis (DVT) and pulmonary embolus are major causes of hospital-related morbidity and mortality, and are recognized as complications in patients with traumatic injury. Despite the significant morbidity and mortality associated with DVTs, prophylaxis and treatment are still not well understood and remain the subject of research and debate. Recent findings: Elements of the patient's history and physical examination, along with thromboelastography, can be used to predict patients who are at greatest risk of DVT and venous thromboembolism (VTE). Novel assays and biomarkers hold promise for more accurate evaluation of coagulation status. Patients with traumatic injury are routinely treated with either mechanical or pharmacological treatments to prevent DVT, and a growing body of evidence suggests that DVT prophylaxis should be initiated as early as possible in a patient's hospital course. Summary: In trauma patients with traumatic injury, early identification and targeted VTE prophylaxis in trauma patients may prevent this life-threatening complication.